Русский язык набирает обороты в Гане. «Русский язык за рубежом» №3/2011, стр.100-104, М. Russian Language in Ghana. In: Journal “Russkii Yasik Za Rubezhom” №3/2011, Moscow, Russia, pp.100-104. - Csajbok-Twerefou, I.; Viczai, P. (My University, 2011)
In this article we discuss the teaching of foreign languages in Ghana paying particular attention to the teaching of Russian language in tertiary institutions There are presented main characteristics and some difficulties of teaching foreign languages, more specifically – the teaching of Russian language in the University of Ghana, where one of the authors has taught for more than a decade. We also analyze the teaching conditions of the teaching staff of the department as well as underlining the various activities of the Russian section, its possibilities and forms of co-operations with Russia, and its further plans.
Keywords: University of Ghana; Russian language; system of education; studied disciplines; co-operation; year abroadprogram; Moscow